Cancer Therapy: Programmed Nanoparticle‐Loaded Nanoparticles for Deep‐Penetrating 3D Cancer Therapy (Adv. Mater. 29/2018). Issue 29 (16th July 2018) - Kim, Jinhwan; Jo, Changshin; Lim, Won‐Gwang; Jung, Sungjin; Lee, Yeong Mi; Lim, Jun; Lee, Haeshin; Lee, Jinwoo; Kim, Won Jong
Abstract : In article number1707557, Jinwoo Lee, Won Jong Kim, and co‐workers demonstrate nanoparticle‐loaded nanoparticles comprising large‐pored silica nanoparticles and gold nanoparticles operated by functional DNA. Depending on the pH gradient in the cancer microenvironment, an elaborately programmed DNA transition induces dynamic behavior of the nanoparticle‐loaded nanoparticle with three stages: preferential accumulation in cancerous region, deep penetration into the 3D cancer tissue, and intracellular specific anticancer drug release.